2002
DOI: 10.1007/s10096-001-0676-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Highly Active Antiretroviral Therapy on Fever of Unknown Origin in HIV-Infected Patients

Abstract: In order to assess the impact of highly active antiretroviral therapy (HAART) on the frequency and etiology of fever of unknown origin in HIV-infected patients, a retrospective study was performed on cases of fever of unknown origin observed from January 1997 to December 1999 in seven hospitals in five cities in Andalusia, Spain. During the period specified, a total of 4,858 HIV-infected patients receiving HAART and 2,787 HIV-infected individuals not receiving HAART were studied. The frequency of fever of unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…ART use has been found to be associated in the decline of FUO prevalence. 2,3 Although this study confirms that FUO primarily occurred among persons with advanced HIV/AIDS, it also spotlights gaps in access to ART use in the initial two-year period after universal access to generic combination stavudine, lamivudine and nevirapine (GPO-VIR) became available. 7 Undoubtedly, routine HIV testing in general populations, earlier case identification and promotion of ART use are essential strategies needed in this population.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…ART use has been found to be associated in the decline of FUO prevalence. 2,3 Although this study confirms that FUO primarily occurred among persons with advanced HIV/AIDS, it also spotlights gaps in access to ART use in the initial two-year period after universal access to generic combination stavudine, lamivudine and nevirapine (GPO-VIR) became available. 7 Undoubtedly, routine HIV testing in general populations, earlier case identification and promotion of ART use are essential strategies needed in this population.…”
Section: Discussionmentioning
confidence: 53%
“…4,5 Notably, in populations with access to ART, investigators have reported a decline in the incidence of FUO and opportunistic infections. 2,3 In Thailand, universal access to ART began in April 2002, yet limited data are available for FUO in this era. 6,7 We conducted an observational study of hospitalized adults with FUO and HIV infection to assess the incidence, aetiologies and mortality associated with FUO in the ART era and compared our findings with Thai-based studies from the pre and post-ART era.…”
Section: Introductionmentioning
confidence: 99%
“…[68][69][70][71] Highly active antiretroviral therapy has reduced human immunodeficiency virus associated fevers of unknown origin in the Western world, but has not altered its etiologic spectrum. 72 The relative frequency of causes in human immunodeficiency virus fevers of unknown origin is influenced by highly active antiretroviral therapy, CD4 count, geographical area and endemic infection prevalence, which may provide clues to the diagnosis. Most cases of human immunodeficiency virus fevers of unknown origin are due to infection, and common non-infectious causes are malignancies and drug fevers.…”
Section: Fever Of Unknown Origin In Human Immunodeficiency Virusmentioning
confidence: 99%
“…Fever of unknown origin (FUO) has also been acknowledged as a major issue among these patients (2)(3)(4)(5). The advent of combined highly active antiretroviral therapy (HAART) has largely contributed to the declining morbidity and mortality rates among HIV-infected patients in both resource-rich and resource-constrained countries (6)(7)(8). Recent studies have demonstrated the linkage between reduced incidence of FUO in the HIV-infected patients and the wider availability and access the HAART (9,10).…”
Section: Introductionmentioning
confidence: 99%